Particle disease: Biologic mechanisms of periprosthetic osteolysis in total hip arthroplasty. Issue 2 (April 2013) - Gallo, Jiri; Goodman, Stuart B; Konttinen, Yrjö T; Raska, Milan
Numerous studies provide detailed insight into the triggering and amplification mechanisms of the inflammatory response associated with prosthetic wear particles, promoting final dominance of bone resorption over bone formation in multiple bone multicellular units around an implant. In fact, inflammation is a highly regulated process tightly linked to simultaneous stimulation of tissue protective and regenerative mechanisms in order to prevent collateral damage of periprosthetic tissues. A variety of cytokines, chemokines, hormones and specific cell populations, including macrophages, dendritic and stem cells, attempt to balance tissue architecture and minimize inflammation. Based on this fact, we postulate that the local tissue homeostatic mechanisms more effectively regulate the pro-inflammatory/pro-osteolytic cells/pathways in patients with none/mild periprosthetic osteolysis (PPOL) than in patients with severe PPOL. In this line of thinking, 'particle disease theory' can be understood, at least partially, in terms of the failure of local tissue homeostatic mechanisms. As a result, we envision focusing current research on homeostatic mechanisms in addition to traditional efforts to elucidate details of pro-inflammatory/pro-osteolytic pathways. We believe this approach could open new avenues for research and potential therapeutic strategies.